Reducing Chemical Fertilizer Dependency In Cauliflower Farming For Economic Sustainability - Juhandi, Dany; Elisabeth, Jenny; Sumanto, Natalia Lusianingsih; Mabrur, Muhammad; Nofriadi, Nofriadi; Dithisari, Indri; Yunita, Ananda; Hutapea, Widya Yohana (Jambura Agribusiness Journal, 2025)
Fertilizer application is a crucial aspect of agricultural practices, especially for horticultural crops like cauliflower. Humbang Hasundutan Regency, a key horticultural hub in North Sumatra Province, has been significantly affected by rising chemical fertilizer costs, placing a financial strain on farmers. This study aimed to evaluate three fertilization strategies in terms of cost-efficiency, effectiveness, and their potential to reduce chemical fertilizer expenses. Using an experimental method, primary data were collected over one growing season to assess the efficiency and effectiveness of each experiment. Results showed that combining chemical and organic fertilizers improved cost-efficiency but did not enhance production effectiveness. Specifically, a 50:50 blend of chemical and organic fertilizers reduced fertilizer costs by IDR 1,468,400 per hectare. These findings indicate that incorporating organic fertilizers can be a viable approach for farmers to lower input costs and potentially improve farm sustainability.